2018
DOI: 10.1038/s41598-018-28337-6
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic capecitabine vs. best supportive care in Child-Pugh B hepatocellular carcinoma: a proof of concept

Abstract: There is a relative lack of evidence about systemic treatments in patients with hepatocellular carcinoma (HCC) and moderate liver dysfunction (Child-Pugh B). In this multicenter study we retrospectively analyzed data from Child-Pugh B-HCC patients naïve to systemic therapies, treated with MC or best supportive care (BSC). To reduce the risk of selection bias, an inverse probability of treatment weighting approach was adopted. Propensity score was generated including: extrahepatic spread; macrovascular invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…For example, a real-world cohort study and a case series investigating nivolumab in HCC CBP patients (including 71 and 18 such patients, respectively, mostly in the second-line setting) demonstrated CR rates of 0% and 6%, respectively, and PR rates of 3% and 11%, respectively [ 19 , 20 ]. Metronomic capecitabine (MC) treatment (i.e., chronic administration of capecitabine at low doses without prolonged drug-free breaks) also showed promising results in two retrospective studies of which only one included only HCC CBP patients [ 21 , 22 ]. This retrospective analysis compared MC ( n = 35) to best supportive care (BSC; n = 70) in treatment-naïve CPB patients and demonstrated significantly improved OS with MC vs. BSC (7.5 vs. 5.1 months; p = 0.013) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a real-world cohort study and a case series investigating nivolumab in HCC CBP patients (including 71 and 18 such patients, respectively, mostly in the second-line setting) demonstrated CR rates of 0% and 6%, respectively, and PR rates of 3% and 11%, respectively [ 19 , 20 ]. Metronomic capecitabine (MC) treatment (i.e., chronic administration of capecitabine at low doses without prolonged drug-free breaks) also showed promising results in two retrospective studies of which only one included only HCC CBP patients [ 21 , 22 ]. This retrospective analysis compared MC ( n = 35) to best supportive care (BSC; n = 70) in treatment-naïve CPB patients and demonstrated significantly improved OS with MC vs. BSC (7.5 vs. 5.1 months; p = 0.013) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the anatomical classification of BTC may be considered simplistic, it faithfully reflects the differentiation of BTC subgroups in terms of epidemiology, etiology, clinical presentation, molecular features and therapeutic approaches (6,7). BTC currently represents about 3% of all gastrointestinal malignancies and the second most common primary liver cancer (PLC), following hepatocellular carcinoma (HCC) (8,9). Even though BTC is considered an uncommon cancer in Western countries, its incidence is increasing, and perhaps is associated with the increasing incidence of iCCA and partly as a result of better disease recognition (10)(11)(12).…”
Section: Abstract Peripheral Blood Of Cancer Patientsmentioning
confidence: 99%
“…Generally, based on chronic hepatitis B or C virus infection in China, HCC patient treatments were limited not only by advanced or end stage at diagnosis but also by poor liver function. Previous studies (13)(14)(15) have shown that poor Child-Pugh scores affect not only choice of treatment but also the prognosis of HCC patients. Decompensated liver cirrhosis patients may be more at risk of dying from cirrhosis complications than from tumor dissemination.…”
Section: Discussionmentioning
confidence: 99%